Comparison of the h‐Index Scores Among Pathogens Identified as Emerging Hazards in North America. Issue 1 (16th April 2014) - Cox, R.; McIntyre, K. M.; Sanchez, J.; Setzkorn, C.; Baylis, M.; Revie, C. W.
Summary: Disease surveillance must assess the relative importance of pathogen hazards. Here, we use the Hirsch index ( h‐ index) as a novel method to identify and rank infectious pathogens that are likely to be a hazard to human health in the North American region. This bibliometric index was developed to quantify an individual's scientific research output and was recently used as a proxy measure for pathogen impact. Analysis of more than 3000 infectious organisms indicated that 651 were human pathogen species that had been recorded in the North American region. The h‐ index of these pathogens ranged from 0 to 584. The h‐ index of emerging pathogens was greater than non‐emerging pathogens as was the h‐ index of frequently pathogenic pathogens when compared to non‐pathogenic pathogens. As expected, the h‐ index of pathogens varied over time between 1960 and 2011. We discuss how the h‐ index can contribute to pathogen prioritization and as an indicator of pathogen emergence.